AQUEOUS SPECIATION OF YTTRIUM AT TEMPERATURES FROM 25 TO 340°C AT PSAT: AN IN SITU EXAFS STUDY - Ragnarsdottir K.V.; Sherman D.M.; Collins C.R.; Odkers E.H. (My University, 1998)
The solvation environment of aqueous yttrium in chloride bearing solutions was characterised by EXAFS spectroscopy at temperatures from 25 to 340°C. Four solution compositions were considered containing 0.1 M YCl3, 0.1 M YCl3+0.23 M HCl+1.0 M NaCl, 0.1 M YCl3+0.23 M HCl+2.0 M NaCl, and 0.05 M Y(NO3)3, respectively. Yttrium was found to be surrounded by an inner coordination shell of H2O, the coordination number decreasing from 9–10 to ∼8 with increasing temperature from 25 to 340°C. The Y–O interatomic distance is constant 2.37±0.02 Å at temperatures up to 340°C. Yttrium chloride inner sphere complexing is negligible up to 340°C for all solutions, including that containing 2.5 M chloride. This observation implies that chloride inner sphere complexes play an insignificant role in the solubility and transport of yttrium, and by analogy the heavy rare-earth elements in sub critical crustal fluids. Data analysis of EXAFS spectra of the 0.1 M YCl3 solution at temperatures in excess of 250°C indicate the presence of yttrium atoms located at ~3.6 Å and ~4.9 Å from the central yttrium atom. This latter observation is consistent with yttrium polyatomic species formation, or polymerisation.